2010
DOI: 10.1007/s11103-010-9698-0
|View full text |Cite
|
Sign up to set email alerts
|

An ordered EST catalogue and gene expression profiles of cassava (Manihot esculenta) at key growth stages

Abstract: A cDNA library was constructed from the root tissues of cassava variety Huanan 124 at the root bulking stage. A total of 9,600 cDNA clones from the library were sequenced with single-pass from the 5'-terminus to establish a catalogue of expressed sequence tags (ESTs). Assembly of the resulting EST sequences resulted in 2,878 putative unigenes. Blastn analysis showed that 62.6% of the unigenes matched with known cassava ESTs and the rest had no 'hits' against the cassava database in the integrative PlantGDB dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…This observation was consistent with previous reports showing that the stress response-related genes were expressed at high levels relative to the plant's ability to grow in harsh environments (Li et al 2010).…”
Section: Functional Analysis Of Significant Genes During Phase Transisupporting
confidence: 93%
“…This observation was consistent with previous reports showing that the stress response-related genes were expressed at high levels relative to the plant's ability to grow in harsh environments (Li et al 2010).…”
Section: Functional Analysis Of Significant Genes During Phase Transisupporting
confidence: 93%
“…A number of excellent studies have indicated that metabolic processes were among the most regulated during developing stages of plants, and these genes were involved in many biological processes: e.g. glycan biosynthesis and metabolism, and the metabolisms of carbohydrates, lipids, amino acids and energy [26,44,45,60,61]. In developing bamboo culm in the present study, the dominant metabolic processes (27 unigenes) included glycan biosynthesis and metabolism, the metabolisms of carbohydrates, lipids, amino acids, nucleotides, energy and biosynthesis of other secondary metabolites (Additional file 12: Table S7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many molecular studies on drought responses have used a single genotype without comparing the expression of genes between contrasting genotypes (Sakurai et al . 2007; Guo et al 2009; You-Zhi et al . 2010), making it difficult to separate drought-tolerance-related genes from drought-responsive genes.…”
Section: Discussionmentioning
confidence: 99%